Determinants Of Contraceptive Method Choice Among Reproductive-Age Couples: A Literature Review Of Socioeconomic And Health Service Factors - Ketut Anom Sri Kesumawati; Kurniati Devi Purnamasari; Ni Kadek Flora Ayu Dwi Indahsari; Dedah Haryani (Universitas Galuh, 2025)
Background: Family Planning (FP) is an effort to regulate the birth rate, spacing, and number of children to improve maternal and family health. The choice of contraceptive method is a key factor in the success of the FP program, but its use among couples of childbearing age is still not optimal. Methods: This study used a literature review method by examining scientific articles from the Google Scholar, PubMed, and ScienceDirect databases published in the last 10 years (2015–2025). A total of n = 15 articles that met the inclusion criteria were described using a narrative synthesis approach. Results: The results showed that the choice of contraceptive method was influenced by various factors, including knowledge, education level, age, parity, husband's support, access to health services, and perceptions of contraceptive side effects. These factors interact with each other in determining the decision of couples of childbearing age in choosing a contraceptive method. Conclusion: The choice of contraceptive method is influenced by individual, social, and health service factors. Therefore, comprehensive education, increased involvement of partners (especially husbands), and strengthening access and quality of FP services are needed to increase the use of appropriate and sustainable protection methods.